(untitled) - Foley, Barbara H. (Boston, MA., 2004)
English in Action is a four-level core language series for secondary and adult students. Students master listening, speaking, reading, writing, and grammar through a variety of lively, classroom-tested, easy-to-use activities.
Keywords: English language,English language; Grammar,Problems, exercises, etc